Cores of combined games - Francis Bloch; Geoffroy De Clippel (Brown University, Department of Economics, 2008)
This paper studies the core of combined games, obtained by summing two coalitional games. It is shown that the set of balanced transferable utility games can be partitioned into equivalence classes of component games to determine whether the core of the combined game coincides with the sum of the cores of its components. On the other hand, for non-balanced games, the binary relation associating two component games whose combination has an empty core is not transitive. However, we identify a class of non-balanced games which, combined with any other non-balanced game, has an empty core.
Keywords: C70; C71; 330; Cooperative Games; Core; Additivity; Issue Linkage; Multi Issue Bargaining; Kooperatives Spiel; Core; Koalition; Verhandlungstheorie; Theorie